Investigating The Link Between Sitting Habits And Low Back Pain In Administrative Staff: A Cross-Sectional Study - Muhajir Muhajir; Nurwalmi Nurwalmi; Darwis Durahim; Syamsuddin Syamsuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The research aims to determine the relationship between sitting habits (position and duration) and the occurrence of low back pain in administrative employees at the Regional General Hospital of Prof. Dr. H. M. Anwar Makkatutu Bantaeng Regency in 2024. This study employs a quantitative descriptive design with cross-sectional study. A sample of 28 participants from 30 populations based on inclusion criteria using total sampling techniques. Data analysis used the chi-square test (X2) and Spearman's rank correlation coefficient (ρ) with a confidence level of 95%. Based on the analysis, there is a relationship between sitting position and the incidence of low back pain (p= 0.025), the level of relationship is moderate (ρ=0,573), and there is a relationship between sitting duration and the occurrence of low back pain (p= 0.044), the level of relationship is moderate (ρ=0.534).